Meningkatkan Minat Belajar Anak Dengan Metode Diskusi Sambil Bermain Ice Breaking - Nadila Tri Ramadani; Hairani Siregar (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Children's interest in learning has recently decreased drastically due to boring children's learning methods and replaced by online games which are very interesting among children. This will become a very serious problem if it continues. The problem of interest in learning which, according to him, also occurs at the Pintu Harapan Medan orphanage. Because of this, the process of providing assistance was carried out through practicum 1 student of social welfare science faculty of social science and political science, University of North Sumatra by applying the discussion method while playing ice breaking, this method has the aim of increasing children's concentration and eliminating boredom in children. Besides that, a mini project was also carried out at this practicum, namely by making an intervention, specifically a micro intervention that aims to help one of the orphans in solving the problems that they are experiencing.